2022
DOI: 10.1371/journal.pone.0268574
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of pure hybridogenetic water frog populations: Genotypic variability in progeny of diploid and triploid parents

Abstract: An intriguing outcome of hybridisation is the emergence of clonally and hemiclonally reproducing hybrids, that can sustain, reproduce, and lead to the emergence of polyploid forms. However, the maintenance of diploid and polyploid hybrid complexes in natural populations remains unresolved. We selected water frogs from the Pelophylax esculentus complex to study how diploid and triploid hybrids, which reproduce hemiclonally via hybridogenesis, are maintained in natural populations. During gametogenesis in diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This repetitive sequence was observed in the pericentromeric region of 5 large and one heterobranchial medium-small chromosome (no. 8) (Ragghianti et al, 1995(Ragghianti et al, , 2004, while others reported its presence in all 13 chromosomes of P. ridibundnus, but with different intensity of signals (7 chromosomes exhibit strong signals, 6 chromosomes exhibit weak signal) (Marracci et al, 2011;Dedukh et al, 2020b;Dedukh et al, 2022b). Moreover, we detected signals in diploid and triploid P. esculentus in interphase nuclei of somatic and germ cells which significantly improved our analysis.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…This repetitive sequence was observed in the pericentromeric region of 5 large and one heterobranchial medium-small chromosome (no. 8) (Ragghianti et al, 1995(Ragghianti et al, , 2004, while others reported its presence in all 13 chromosomes of P. ridibundnus, but with different intensity of signals (7 chromosomes exhibit strong signals, 6 chromosomes exhibit weak signal) (Marracci et al, 2011;Dedukh et al, 2020b;Dedukh et al, 2022b). Moreover, we detected signals in diploid and triploid P. esculentus in interphase nuclei of somatic and germ cells which significantly improved our analysis.…”
Section: Discussionsupporting
confidence: 57%
“…Hybridogenetic gametogenesis usually occurs in females, except of diploid fish Hypseleotris spp (Schmidt et al, 2011;Majtánová et al, 2021) and triploid green toad Bufotes pseudoraddei baturae (Stöck et al, 2002(Stöck et al, , 2012 where both sexes eliminate one of the genomes. The same process evidently also occurs in male P. esculentus, although it was proven in most cases indirectly by analysis of genome composition in progeny resulting from experimental crosses between parental species and hybrids, as evidenced by classic studies of Berger (Berger, 1968(Berger, , 1973(Berger, , 1976 and others (Dedukh et al, 2017;Dedukh et al, 20220b;Dedukh et al, 2022b). The other evidence comes from studies on genome compositions of spermatozoa detected by flow cytometry that allowed distinguishing genomes on the basis of species-specific difference in amount of DNA in P. lessonae and P. ridibundus (Mazin and Borkin, 1979;Vinogradov et al, 1990;Biriuk et al, 2016).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations